KEMITRAAN SEKOLAH DAN DUNIA USAHA DALAM PERENCANAAN PROGRAM PENDIDIKAN DI SDN PELAMBUAN 4 BANJARMASIN - Anugrah Mitria Sari; Arinda Oktanthia Wijaya; Suhaimi; Sulistiyana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the partnership between SDN Pelambuan 4 Banjarmasin and PT Trakindo Utama in supporting educational planning at the elementary school level. School–industry partnerships are increasingly recognized as an important strategy to strengthen educational quality through collaboration with external stakeholders. This research employed a qualitative approach with data collected through observation, in-depth interviews, and documentation. The research subjects consisted of the principal, teachers, and related parties involved in the partnership program at SDN Pelambuan 4 Banjarmasin. The findings indicate that the partnership with PT Trakindo Utama has contributed significantly to educational planning through several activities, including teacher training, facilitation of school program development, and provision of infrastructure support through Corporate Social Responsibility (CSR) programs. The partnership also involves facilitators and external partners who assist schools in developing innovative programs, such as literacy programs, project-based learning, child-friendly school initiatives, and mental health awareness programs. In addition, the collaboration encourages participatory planning processes involving school stakeholders through workshops, brainstorming sessions, and program evaluations. Overall, the partnership has strengthened school programs, improved teachers’ professional capacity, supported educational facilities, and stimulated innovative programs within the school. Therefore, school–industry partnerships can be considered an effective strategy to support educational planning and improve the quality of education at the elementary school level.